Enhancing Financial Efficiency in Higher Education Institutions: A Case Study on Implementing an ERC-20 Token as a University-Specific Currency - Isaac, Umaru Emmanuel (Kwaghe International Journal of Sciences and Technology, 2025)
This paper aims to investigate the potential benefits and feasibility of implementing a decentralized financial transaction system on the Ethereum blockchain for higher educational institutions. The primary motivation behind this research is to explore the cost-effectiveness and advantages of transitioning from traditional server-based systems to blockchain technology. Additionally, the study evaluates the advantages of introducing a digital currency (MUCoins) for students, in this case Mewar university India, enhancing the control and flexibility over financial transactions on campus, enabling the university to accommodate more facilities that generate income.